2021
DOI: 10.3390/plants10020241
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of As, Ag, Cd, Cu, Pb, and Zn by Native Plants Growing in Soils Contaminated by Mining Environmental Liabilities in the Peruvian Andes

Abstract: The capability of native plant species grown in polluted post-mining soils to accumulate metals was evaluated in view of their possible suitability for phytoremediation. The study areas included two environmental liabilities in the Cajamarca region in the Peruvian Andes. The content of As, Ag, Cd, Cu, Pb, and Zn was determined in individual plant organs and correlated with soil characteristics. The degree of the pollution depended on the metal with results ranging from uncontaminated (Cd) to moderately (Zn), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…Table 5 shows the metal concentrations and bioconcentration factors (BCFs) of six plants in C3 water samples. The BCF indicates the ability of plants to enrich heavy metals from their surroundings [33], and it could be seen that the BCFs of six plants for each metal were greater than one, indicating that the accumulation of metals in plant tissues was greater than that in the growth medium, so all six plants could be used for phytoextraction of Mn, Zn, and Cd [34]. The order of BCF for most of the plants (except P. australis) was Mn > Cd > Zn, which indicated that Mn was more readily absorbed by plants, thus explaining the decrease in Mn removal in AMD due to the poor growth state of plants at the later stages of the experiment.…”
Section: Removal Mechanism Of Pollutants In Amdmentioning
confidence: 99%
“…Table 5 shows the metal concentrations and bioconcentration factors (BCFs) of six plants in C3 water samples. The BCF indicates the ability of plants to enrich heavy metals from their surroundings [33], and it could be seen that the BCFs of six plants for each metal were greater than one, indicating that the accumulation of metals in plant tissues was greater than that in the growth medium, so all six plants could be used for phytoextraction of Mn, Zn, and Cd [34]. The order of BCF for most of the plants (except P. australis) was Mn > Cd > Zn, which indicated that Mn was more readily absorbed by plants, thus explaining the decrease in Mn removal in AMD due to the poor growth state of plants at the later stages of the experiment.…”
Section: Removal Mechanism Of Pollutants In Amdmentioning
confidence: 99%
“…None of the species reached the hyperaccumulation threshold of As, which is > 1000 mg kg −1 DW according to Ghaderian, Lyon [ 52 ]. Cruzado-Tafur, Bierla [ 53 ] also reported low As accumulation in the aboveground parts in several species collected from the Ag–Pb/Zn site in the Hualgayoc district (northern Peru), such as Hypericum laricifolium (2.01 mg kg −1 ), Achyrocline alata (3.82 mg kg −1 ), Arenaria digyna (3.93 mg kg −1 ), Calamagrostis recta (3.99 mg kg −1 ), Puya sp. (5.12 mg kg −1 ), Ageratina glechonophylla (6.44 mg kg −1 ), and Chusquea scandens (4.76 mg kg −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering this, further studies should focus on the specific characteristics of local rivers used for animal drinking, metal concentrations All this suggests that bioaccumulation in mammals is not well studied in the country; similarly, it is important to know how these animals are affected by the ingestion of contaminated plant-based feed or contaminated water. In fact, though not being part of this review, Peruvian authors have reported metal contents (Hg, Al, As, Ba, Cd, Cr, Ni, and Pb) in plant species commonly used for forage (e.g., [76,92,[139][140][141][142][143][144][145][146][147][148][149][150]) that could contribute to bioaccumulation in edible mammals. Considering this, further studies should focus on the specific characteristics of local rivers used for animal drinking, metal concentrations in soils, and forage-type plants that farmers use to feed domestic mammals or regions where range-free mammals naturally exist.…”
Section: Mammalsmentioning
confidence: 99%